Heuristic algorithm for virtual path based ATM networks - Kumaran Veerayah. (2008)
This report evaluates the performance of a heuristic algorithm for dynamic allocation of virtual path (VP) bandwidth in an ATM network. A new VP concept, where the VPs are used to provide logical direct connections between any two switching nodes through intermediate cross-connect nodes in the network, is introduced. Each ATM switch is connected to every other ATM switch by multiple pairs of VPs. Each directed ATM switch pair, known as demand pair, is offered with multiple classes of traffic with different bandwidth requirement.